(untitled) (Al-Farooq Journal of Sciences, 2026)
It has been demonstrated that tachyon particles travel at speeds significantly greater than the speed of light, following a quadratic rather than a linear law. This is illustrated through the application of the tachyon Lorentz factor in verse 4 of Surah Al-Ma’arij. Furthermore, a unified theory has been proposed to calculate the normal speed of light alongside tachyon speed, particularly in relation to verses 5 of Surah As-Sajdah and 4 of Surah Al-Ma’arij. The numerical results from this theory have shown promise. These findings reinforce the notion that the speed of light remains constant in both verses, while tachyon speed reveals a minimum value in verse 5 of Surah As-Sajdah and a maximum value in verse 4 of Surah Al-Ma’arij. Such discoveries are unprecedented in both theoretical physics and the study of scientific miracles, representing significant evidence that could enable physicists to develop a theory of particles that travel faster than light, known as tachyons. In this research, the speed of tachyon is explained in more detail, as the speed of light has already been thoroughly addressed in our reference [9].